Discovery of a new series of imidazo[1,2-a]pyridine compounds as selective c-Met inhibitors - Liu Tong-chao; Peng Xia; Ma Yu-chi; Ji Yin-chun; Chen Dan-qi; Zheng Ming-yue; Zhao Dong-mei; Cheng Mao-sheng; Geng Mei-yu; Shen Jing-kang; Ai Jing; Xiong Bing (Acta Pharmacologica Sinica, 2017)
Aim: Aberrant c-Met activation plays a critical role in cancer formation, progression and dissemination, as well as in development of resistance to anticancer drugs. Therefore, c-Met has emerged as an attractive target for cancer therapy. The aim of this study was to develop new c-Met inhibitors and elaborate the structure-activity relationships of identified inhibitors. Methods: Based on the predicted binding modes of Compounds5 and 14 in docking studies, a new series of c-Met inhibitor-harboring 3-((1H-pyrrolo[3,2-c]pyridin-1-yl)sulfonyl)imidazo[1,2-a]pyridine scaffolds was discovered. Potent inhibitors were identified through extensive optimizations combined with enzymatic and cellular assays. A promising compound was further investigated in regard to its selectivity, its effects on c-Met signaling, cell proliferation and cell scattering in vitro. Results: The most potent Compound 31 inhibited c-Met kinase activity with an IC50 value of 12.8 nmol/L, which was >78-fold higher than those of a panel of 16 different tyrosine kinases. Compound 31 (8, 40, 200 nmol/L) dose-dependently inhibited the phosphorylation of c-Met and its key downstream Akt and ERK signaling cascades in c-Met aberrant human EBC-1 cancer cells. In 12 human cancer cell lines harboring different background levels of c-Met expression/activation, Compound 31 potently inhibited c-Met-driven cell proliferation. Furthermore, Compound 31 dose-dependently impaired c-Met-mediated cell scattering of MDCK cells. Conclusion: This series of c-Met inhibitors is a promising lead for development of novel anticancer drugs.